2021
DOI: 10.1021/acsami.1c11858
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Fenton-Like Catalysis Boosting the Antifouling Performance of the Heterostructured Membranes Fabricated via Vapor-Induced Phase Separation and In Situ Mineralization

Abstract: A photocatalytic membrane with significant degradation and antifouling performance has become an important part in wastewater treatment. However, the low catalyst loading on the polymer membrane limits its performance improvement. Herein, we fabricated poly­(vinylidene fluoride) (PVDF) and poly­(acrylic acid) (PAA) blend membranes with a rough surface via a vapor-induced phase separation (VIPS) process. Then Fe3+ was cross-linked with the carboxyl groups on the membrane surface and further in situ mineralized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…49 Figure S5b shows the high-resolution XPS spectra for the O 1s region. The principal peaks of Fe−O (lattice Fe-binding oxygen, 529.7 eV), Fe−OH (lattice hydroxyl, 531.2 eV), C−O (532.5 eV), and C−O (534.2 eV) are observed at the typical positions 53,56. The results show that FeOOH was successfully grown on the CK coating during incubation.We tried to explore the trend of PP-(CK-Fe) surface elements by EDS.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…49 Figure S5b shows the high-resolution XPS spectra for the O 1s region. The principal peaks of Fe−O (lattice Fe-binding oxygen, 529.7 eV), Fe−OH (lattice hydroxyl, 531.2 eV), C−O (532.5 eV), and C−O (534.2 eV) are observed at the typical positions 53,56. The results show that FeOOH was successfully grown on the CK coating during incubation.We tried to explore the trend of PP-(CK-Fe) surface elements by EDS.…”
mentioning
confidence: 82%
“…47,49 A broad peak appears at 3000−3500 cm −1 of PP-CK and PP-(CK-Fe), which belongs to adsorbed water, hydroxyl, or amino groups. 32,53,54 To characterize the changes in amino groups on the coating before and after incubation, we used the classical ninhydrin color test. 55 The results showed that amino groups were present on C2K4 but disappeared on C2K4-Fe (Figure S3).…”
Section: Physicochemical Characterization Of Pp-ck and Pp-(ck-fe)mentioning
confidence: 99%
“…The membrane was thoroughly washed using distilled water after emulsion filtration, and the pure water flux was tested again to evaluate the membrane's efficiency. Equation () was used to calculate the oil rejection 41 Rejection0.12em()%goodbreak=CfCpCfgoodbreak×100, where C p and C f denote the permeate and feed emulsion concentrations, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The flux recovery ratio (FRR) was measured by Equation () 41 FRR0.12em()%goodbreak=JW2JW1goodbreak×100, where J W 1 is the water flux before oil rejection study and J W 2 is water flux after oil rejection study.…”
Section: Methodsmentioning
confidence: 99%
“…Hao Yang et al used AIBN to initiate the aggregation of acrylic acid (AA) and grafting onto PVDF, and then immersed the PVDF/PAA membrane in FeCl 3 /HCl solution for further generation into 𝛽-FeOOH nanorods. [72] The carboxyl group on PAA can form a stable coordination with Fe 3+ , which induces in situ crystalline mineralization of 𝛽-FeOOH on the membrane. This dynamic metal coordination reduces the energy barrier for the binding of Fe 3+ to organisms, facilitating the aggregation, nucleation, and crystallization of 𝛽-FeOOH.…”
Section: Interfacial Compatilization Inducing Mineralizationmentioning
confidence: 99%